PERILAKU SOSIAL ANAK USIA DINI DI KAMPUNG NELAYAN (Penelitian Etnografi Anak Usia 5-6 Tahun di Pulau Untungjawa Kepulauan Seribu, 2015) - Nopa Wilyanita (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2016)
This study aims to describe the form of social behavior teaching in fishing villages, the process of cultivating social behavior for children aged 5-6 years and to describe the inhibiting and supporting factors of early childhood social behavior. This research method uses qualitative ethnography. The subjects of this study were four children from the 5-6 years old One Roof Kindergarten Kindergarten. This research was conducted on Untungjawa Island, Thousand Islands, Jakarta. The results of the research findings show that there are also forms of teaching on social behavior in the fishing community of Untungjawa Island, namely: Religion as a role model that must be obeyed, Having an attitude of helping each other, Feeling what other people feel, Do not make a fuss so work together, Do not take property other people, which is not our right. Factors that influence early childhood social behavior are factors that support the important role of teachers and the learning process, school rules that can shape positive social behavior. The supporting factors of the family are the role of parents in educating children to shape social behavior and finally the supporting factors of the community environment, namely the formation of a healthy environment, comfort for children to interact with peers, the attention of the local community on the growth and development of children in the environment